Model Reference Control for an Economic Growth Cycle Model - Pengfei Zhao; Cai Liu; Xuan Feng (Journal of Applied Mathematics)
A useful method in intelligent engineering, called model reference control (MRC), is applied in an economic control problem. The authors review the main framework of MRC and Goodwin growth cycle (GGC) model between two countries and drive the employment rate to be approximate stable in a high level by controlling the workers' share in the national income automatically. It is very helpful to constitute economic policies for a country or an economic union.